The Effect of Graphite and Activated Carbon as Dispersed Particle in Base Fluid as Quench Medium on the Hardness of S45C Carbon Steel - Putra, Wahyuaji Narottama; Somadinata, Danika Aprilia; Ramahdita, Ghiska (UI Scholars Hub, 2023)
Adding a solid particle dispersion into a base fluid could increase its thermal conductivity, hence increasing the heat transfer characteristics. One example of this thermally enhanced fluid is in heat treatment industry as quench medium. By controlling the amount of the dispersed particle, the cooling rate of the quench medium can be altered, and could affect steel hardness after heat treatment. In this research, the dispersed particle used was commercially available graphite and activated carbon particle. As for the base fluid, distilled water and common engine oil were compared. The concentration of the dispersed particle was 0.1, 0.3, 0.5 weight percent. The highest hardness was achieved at 728 HV on the 0.1% activated carbon particle in water base fluid. Meanwhile, by using graphite, the highest hardness achieved was at 639 HV on the 0.1% particle in water base fluid. The result may suggest that activated carbon could improve the cooling rate better due to its impurities. As expected, quenching by dispersed graphite particle in oil based resulted in lower hardness on all variables.